Regional and structural factors in Swedish regional growth during the 1990s - Li Wenjuan (Unité Mixte de Recherche 8504 Géographie-cités, 2006)
Based on the Swedish Standard Industrial Classification and individual longitudinal data, by using the shift-share analysis method, Swedish regional employment growth during the 1990s has been decomposed into two components—growth due to an endogenous regional factor and growth due to an exogenous structural factor. The regional factor is more important in shaping regional growth than the structural factor as indicated by employment, although the two factors both have a positive relation to regional growth. The structural factor creates a macro milieu for a region and the regional factor generates a micro milieu for industries inside the region. The response of core regions to the economic downturn and recovery in Sweden in the period studied is stronger than that of periphery regions. The findings from this study support endogenous growth theories and core-periphery theory.